Erken Laboratory Environmental Monitoring Program - Erken metadata - Department of Ecology and Genetics, Uppsala University (Uppsala University, 2021)
The Erken Laboratory is located at the south-east shore of the lake Erken 70 km north-east of Stockholm. The station has an extensive environmental monitoring program for Lake Erken, including both manual and high-frequency automatic measurements, and participates in research initiates that investigate effects of climate change in lake ecosystems. The monitoring programme includes measurements of physical and chemical parameters, phytoplankton, and since 2014, greenhouse gas fluxes. The station also offers facilities for the implementation of experiments (e.g. mescocoms).

Sensor metadata information for Lake Erken from 2011 to 2016.

The Erken Laboratory is located at the south-east shore of the lake Erken 70 km north-east of Stockholm. The station has an extensive environmental monitoring program for Lake Erken, including both manual and high-frequency automatic measurements, and participates in research initiates that investigate effects of climate change in lake ecosystems. The monitoring programme includes measurements of physical and chemical parameters, phytoplankton, and since 2014, greenhouse gas fluxes. The station also offers facilities for the implementation of experiments (e.g. mescocoms).

Metadata för sensorinformation för Erkensjön under perioden 2011-2016.
Erkenlaboratoriet Monitoringprogrammet - Erken metadata
Keywords: climate; klimat; lakes; sjöar; conservation areas; naturvårdsområden; water resources management; förvaltning av vattenresurser; landscape conservation; naturvård; man-made climate change; klimatförändring orsakad av människan; biological water balance; biologisk balans i vatten; water quality; kvalitet på vatten; climate change impact; klimatförändringarnas konsekvenser; Bio-geographical regions; Biogeografiska regioner; Hydrography; Hydrografi; NATURAL ENVIRONMENT; NATUR OCH MILJÖ; Environment and conservation; Miljö och naturvård; Climate Science; Klimatvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Inland Waters; Sjöar och vattendrag